Chapter Gli scenari - Bellanca, Nicolò (Studi e saggi, 2020)
Chapter seven analyzes some of the most relevant future scenarios, regarding population, energy resources, public health, inequality, democracy on a national scale and forms of social power. On the population, evidences are advanced which cast doubt on the comforting idea that its trend will first become stationary and then decrease. On public health, the connotations of the Covid-19 pandemic are compared with those of the major ecological problems. On inequality, the emphasis is placed on that resulting from competition for the goods of status and power. On democracy, the tension between the national context, in which this political regime has expressed itself in our era, and global processes is discussed. Finally, the coexistence of various forms of social power and the ways in which they combine with each other is examined.